Pemutihan Kertas Koran Bekas dengan Menggunakan Asam Peroksida dalam Media Asam Asetat - Sri Hidayati; Ahmad Sapta Zuidar; Rachmania Widyastuti (AGROINTEK, 2018)
Used newsprint is one of the most potential materials to be recovered into pulp raw material. The problem is the color of newsprint that requires bleaching process. One of the oxidizing agents used for bleaching is the peroxide acid in the acetic acid medium. The purpose of this research is to know the effect of peroxide acid concentration in acetic acid media and the duration of heating to the chemical properties of pulp produced. The best results were obtained at 12% per oxide acid concentration in acetic acid medium and 5 hour heating time, yielding 58.653% cellulose, hemicellulose 9,033%, lignin 22,683%, and color score 4,503% (rather white).